The Significance of the Implicating Learning Quality by Differentiated Learning Method at Junior High School Level in Banjarbaru City - Salim, Agus; Sufyadi, Susanti; Utama, Agus Hadi (Indonesian Journal of Instructional Media and Model, 2023)
The aim of this study is for teachers to be able to implement the IKM program, especially in implementing differentiated learning strategies at the junior high school level in Banjarbaru City, because this is one of the core academic competencies of the IKM program that teachers need to master. This study uses an as-sociative method, with a descriptive approach, and the type of research is quantitative. The associative method is a research method that aims to determine the influence or reciprocal relationship between two or more variables. In this study, the associative method was used to determine the effect of implementing differentiated learning strategies on teacher performance, school culture, and learning quality. Methods and data collection instruments in the form of interactive interviews, training observations, documentation studies, and feedback questionnaires on training activities, related to how teachers strategies in formulating learning outcomes, becoming learning objectives, and how to achieve these differentiated learning objectives. The results show that there is a positive influence of applying differentiated learning strategies between teacher performance and school culture, while there is no significant effect on the quality of learning. The teachers have been able to emphasize differentiated learning strategies that are centered on student learning outcomes, where to find out student learning achievements, teachers have been able to carry out formative assessments at the beginning of learning.